Breast carcinoma with an Oncotype Dx recurrence score <18: Rate of distant metastases in a large series with clinical follow‐up. Issue 1 (15th August 2016) - Wen, Hannah Y.; Krystel‐Whittemore, Melissa; Patil, Sujata; Pareja, Fresia; Bowser, Zenica L.; Dickler, Maura N.; Norton, Larry; Morrow, Monica; Hudis, Clifford A.; Brogi, Edi
Abstract : BACKGROUND: A 21‐gene expression assay (Oncotype DX recurrence score [RS]) that uses reverse transcriptase‐polymerase chain reaction is used clinically in patients with early‐stage, estrogen receptor (ER)‐positive, human epidermal growth factor receptor 2 (HER2)‐negative breast carcinoma (ER+/HER2‐ BC) to determine both prognosis with tamoxifen therapy and the usefulness of adding adjuvant chemotherapy. Use of the assay is associated with reductions in overall chemotherapy use. The current study examined the treatments and outcomes in patients with low RS. METHODS: The authors reviewed the institutional database to identify patients with lymph node‐negative, ER+/HER2‐ BC who were treated at the study institution between September 2008 and August 2013 and their 21‐gene RS results. RESULTS: A total of 1406 consecutive patients with lymph node‐negative ER+/HER2‐ BC and a low RS were identified (510 patients had an RS of 0‐10 and 896 patients had an RS of 11‐17). The median age at the time of diagnosis of BC was 56 years; 63 patients (4%) were aged <40 years. Overall, 1361 patients (97%) received endocrine therapy and 170 patients (12%) received chemotherapy. The median follow‐up was 46 months. Six patients (0.4%) developed distant metastases (1 patient with an RS of 5 and 5 patients with an RS of 11‐17). In the cohorts of patients with an RS of 11 to 17, the absolute rate of distant metastasis among patients aged <40 years was 7.1% (3 of 42 patients) versus 0.2% among patients aged ≥40 years (2 of 854 patients). CONCLUSIONS: The data from the current study document a 0.4% rate of distant metastasis within 5 years of BC diagnosis among patients with lymph node‐negative ER+/HER2‐ BC with an RS <18. Patients aged <40 years at the time of BC diagnosis were observed to have a higher rate of distant metastases. Analysis of data from other studies is necessary to validate this observation further. Cancer 2017;131–137. © 2016 American Cancer Society. Abstract : The current study evaluates the outcome of 1406 patients with early‐stage, lymph node‐negative, estrogen receptor‐positive, human epidermal growth factor receptor 2‐negative breast cancer and an Oncotype Dx recurrence score (RS) <18, and notes a very low rate of distant recurrence at a median follow‐up of 46 months (0.2% among patients with an RS of 0‐10 and 0.6% in patients with an RS of 11‐17). However, among the patients with an RS of 11 to 17, the absolute rate of distant metastasis among patients aged <40 years is 7.1%, versus 0.2% among patients aged ≥40 years.